Pengetahuan Ekosistem dan Perilaku Petani Dalam Mengelola Lahan Pertanian: Pendekatan Psikologi Lingkungan - Akhmad Baidun (‎‎‎TAZKIYA Journal of Psychology, 2003)
Behavior is an individual's response or reaction to an object which is manifested in action, behavior or movement. Behavior is a person's reaction to the surrounding environment, whether simple or complex. However, not all human behavior can be seen, this is because there are behaviors that can be seen directly, and also those that cannot be observed directly. In this case, managing agricultural land is an effort carried out consciously and continuously by farmers. The author wrote this research to see whether there is a positive relationship between farmers and the information they receive in managing agricultural land.